A wet skid resistant tread rubber and a method of making the same
Patent Information
- Application Number
- CN202611186351.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]为此,本发明提供一种抗湿滑胎面橡胶及其制备方法,以解决现有技术中由于工艺控制不够精细和依赖特种原材料而导致的填料与橡胶/树脂间反应不均和成本高、推广难的问题
1. 抗湿滑性能与冰雪性能协同提升,破解性能矛盾
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of tire manufacturing technology, specifically to an anti-slip tread rubber and its preparation method. Background Technology
[0002] Winter tires are primarily used on low-temperature and icy roads, requiring the tread compound to maintain flexibility at low temperatures to increase the contact patch, while simultaneously exhibiting excellent anti-skid performance on wet surfaces to ensure driving safety. However, anti-skid performance and low-temperature performance often present a trade-off: increasing the glass transition temperature of the rubber can improve anti-skid performance near 0°C, but it will reduce flexibility and grip on ice and snow below -20°C; decreasing the glass transition temperature is beneficial for low-temperature performance, but anti-skid performance will decrease accordingly.
[0003] Existing technologies typically employ strategies such as blending rubbers, compounding fillers, and modifying resins to achieve performance balance. However, these methods often fail to achieve sequential control of dispersion followed by reaction, making it difficult to precisely regulate the degree of reaction. The interaction window between modifiers and fillers is limited, resulting in insufficient surface modification of some fillers and a need to strengthen the filler-rubber interface. Furthermore, the tackifying resin used is added at the outset and does not synergize with the modifier. Therefore, improvements in anti-slip performance mainly depend on the selection of fillers and rubber types, limiting the potential for further improvement.
[0004] In addition, existing technologies often face problems such as limited rubber or resin sources and high costs, which are not conducive to large-scale promotion; stringent requirements for mixing processes and equipment; poor dispersion in industrial production; simultaneous modification and dispersion of fillers, which makes it difficult to control the degree of reaction; high temperature may cause partial degradation or excessive cross-linking of resin; and failure to fully realize the synergistic effect between resin and filler.
[0005] In summary, existing technologies either lack precise process control leading to uneven reactions, or rely on special raw materials resulting in high costs and difficulties in widespread adoption. There is a lack of a systematic solution that can achieve synergistic improvement in anti-slip performance and ice and snow performance through refined process design and the use of conventional raw materials. Summary of the Invention
[0006] Therefore, the present invention provides an anti-slip tread rubber and its preparation method to solve the problems of uneven reaction between fillers and rubber / resin, high cost, and difficulty in promotion caused by insufficient process control and reliance on special raw materials in the prior art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a method for preparing anti-slip tread rubber is provided, specifically comprising the following steps: S1, First stage of mixing: Natural rubber, solution-polymerized styrene-butadiene rubber and cis-butadiene rubber are plasticized in a mixer, and then highly dispersed silica, silica dispersant and silane coupling agent are added, mixed and discharged to obtain the first masterbatch. S2, Second stage of mixing: Highly dispersed silica and modified anti-slip resin were added to the first masterbatch and mixed to obtain the second masterbatch. S3, Third Stage Mixing: High abrasion-resistant carbon black N234, active zinc oxide, stearic acid and antioxidant are added to the second masterbatch and then mixed to obtain the third masterbatch. S4, Final Stage: Sulfur and accelerator are added to the third masterbatch, and after mixing and discharging, the mixture is passed through a two-roll mill, sheeted, and cooled to room temperature to obtain anti-slip tread rubber.
[0008] Furthermore, step S1 specifically includes the following steps: the mass fractions of each component are: After plasticizing 40-60 parts of natural rubber, 20-40 parts of solution-polymerized styrene-butadiene rubber, and 10-30 parts of butadiene rubber at room temperature for 1-3 minutes in an internal mixer, add 36-56 parts of highly dispersed silica (which accounts for 60-80% of the total amount of highly dispersed silica used in the entire process of preparing anti-slip tread rubber), 3-8 parts of silica dispersant, and 4-8 parts of silane coupling agent and mix them at 100-120℃ for 2-4 minutes. After desizing, the first masterbatch is obtained. The silica dispersant is a zinc fatty acid soap, and the silane coupling agent is bis-[γ-(triethoxysilane)propyl]tetrasulfide; the specific surface area of the highly dispersed silica is 140-200 m² / g. 2 / g.
[0009] Furthermore, step S2 specifically includes the following steps: The first masterbatch is heated to 120-130℃, and 12-28 parts of highly dispersed silica (which accounts for 20-40% of the total amount of highly dispersed silica used in the entire process of preparing anti-slip tread rubber) and 5-10 parts of modified anti-slip resin are added. The mixture is then mixed at 130-145℃ for 4-6 minutes to allow the silane coupling agent and silica to react fully, while the resin melts and forms a micro-phase separation structure with the rubber matrix, thus obtaining the second masterbatch.
[0010] Furthermore, the modified anti-slip resin mentioned in step S2 is a modified terpene resin, and its preparation specifically includes the following steps: Add α-pinene and bisphenol A separately into a separatory funnel, wash 2-3 times with 5wt% sodium hydroxide aqueous solution, then wash with distilled water until neutral, then add anhydrous magnesium sulfate to dry them separately, and seal for later use. Under nitrogen or argon protection, the treated α-pinene and bisphenol A are added to the reaction solvent and stirred until a homogeneous solution is formed. Then, a cationic catalyst and a molecular weight regulator are added to carry out the cationic polymerization reaction. After the polymerization reaction is completed, excess methanol is added to terminate the reaction. The reaction product is then separated and washed to remove unreacted monomers and catalyst residues. Finally, the product is subjected to vacuum distillation at 250-280℃ for 0.5-3 hours to obtain the modified anti-slip resin.
[0011] Further, the cationic catalyst is one or more of boron trifluoride, aluminum trichloride, and ferric chloride; the molecular weight regulator is one or more of pyridine, 2-methylpyridine, and 2,6-dimethylpyridine; and the reaction solvent is one or more of toluene, xylene, and dichloromethane. The mass-volume ratio of α-pinene, bisphenol A, cationic catalyst, molecular weight regulator and reaction solvent is (1-5)g:(1-5)g:(0.05-0.25)g:(0.5-2.5)g:100mL, and the cationic polymerization reaction is carried out at -20-0℃ for 0.5-3h.
[0012] Furthermore, the modified anti-slip resin has a molecular weight of 1000-1500 Da.
[0013] Furthermore, step S3 specifically includes the following steps: The second masterbatch is cooled to 90-100℃, and 5-20 parts of high abrasion-resistant carbon black N234, 1-3 parts of active zinc oxide, 1-3 parts of stearic acid and 2-5 parts of antioxidant are added. The mixture is then kneaded at 100-110℃ for 2-3 minutes to obtain the third masterbatch. The antioxidant is obtained by mixing antioxidant 4020 and antioxidant RD in a mass ratio of 1:1.
[0014] Furthermore, step S4 specifically includes the following steps: The third masterbatch is cooled to 80-90℃, and 1-2 parts of sulfur and 1-3 parts of accelerator are added. The mixture is then mixed at 90-100℃ for 1-2 minutes. After discharge, the mixture is passed through a two-roll mill 3-5 times, and the sheet is cooled to room temperature to obtain the anti-slip tread rubber. The accelerator is N-tert-butyl-2-benzothiazole sulfenamide.
[0015] According to a second aspect of the present invention, an anti-slip tread rubber is provided, which is prepared by the above-described preparation method.
[0016] According to a third aspect of the present invention, the application of the anti-skid tread rubber prepared by the above-described preparation method is provided in the preparation of snow tires, winter tires or anti-skid tires.
[0017] The present invention has the following advantages: 1. Synergistic improvement in both wet and snow performance, resolving performance contradictions. This invention utilizes a stepwise addition of silica and a segmented temperature-controlled mixing process to ensure the silanization reaction proceeds uniformly with thorough dispersion, constructing a more complete filler-rubber network and effectively reducing the Payne effect. Simultaneously, the micro-phase separation structure formed by the modified anti-skid resin within the rubber matrix generates additional energy dissipation near 0°C, significantly improving anti-skid performance. Furthermore, the resin micro-regions have minimal impact on the glass transition temperature of the continuous rubber phase, maintaining good molecular chain mobility below -20°C, thus simultaneously enhancing grip on ice and snow. Test data shows that the tread rubber prepared in this embodiment achieves a tanδ value of 0.35-0.38 at 0°C and 0.58-0.62 at -20°C, achieving wide-temperature-range synergistic optimization of anti-skid performance and low-temperature performance.
[0018] 2. The silanization reaction sequence is controllable, and the bonding between the filler and rubber interface is enhanced. This invention involves adding silica in two parts at different temperature windows: the first part is added at a low temperature of 100-120℃ for physical dispersion, inhibiting premature silanization; the second part is added after heating to 120-130℃, at which point the silane coupling agent is activated and reacts fully with the surface of fresh silica at 130-145℃. This sequential design of dispersion followed by reaction ensures a more complete and uniform reaction between the coupling agent and silica, significantly improving the surface modification effect of the filler, enhancing the chemical bonding at the filler-rubber interface, and perfecting the filler network structure, ultimately resulting in a comprehensive improvement in the dynamic mechanical properties and abrasion resistance of the rubber compound.
[0019] 3. The ternary synergistic structure of resin, filler, and rubber exhibits significant synergistic effects. In this invention, modified anti-slip resin and silica (part 2) are simultaneously added during the second stage of mixing. The resin is melted and dispersed at 130-145°C, synergizing with the ongoing silanization reaction. Upon cooling, the resin forms nanoscale enriched microdomains that interact with the silica surface through hydrogen bonds or van der Waals forces, jointly constructing a resin-filler-rubber ternary synergistic network. This structure maintains the low-temperature flexibility of the continuous rubber phase while selectively enhancing energy dissipation near 0°C, achieving targeted enhancement of anti-slip performance. The synergistic effect is far superior to the simple superposition of using silica or resin alone.
[0020] 4. Modified terpene resin is a linear polymer obtained by cationic polymerization of α-pinene from natural turpentine oil. It features low molecular weight and high softening point, thus improving various tire performance characteristics. This invention uses bisphenol A as a modifying monomer to copolymerize and modify the terpene resin. Its technical advantages are: (1) Bisphenol A contains two phenolic hydroxyl groups. After its introduction, it can significantly increase the hydroxyl concentration on the surface of terpene resin, improve the bonding force between rubber and water, and thus effectively improve the anti-skid performance of tires. (2) The rigid aromatic ring structure of bisphenol A can increase the softening point and glass transition temperature of the resin, so that the rubber compound can still maintain good mechanical properties at high temperature. (3) By combining with molecular weight regulators, modified terpene resins with molecular weight between 1000 and 1500 and with a narrow molecular weight distribution can be obtained. The resin has good compatibility with the rubber matrix and can form a stable micro-phase separation structure after cooling, generating additional energy dissipation under dynamic strain.
[0021] 5. It has strong process adaptability and good economic efficiency. This invention employs a ternary system combining conventional natural rubber, solution-polymerized styrene-butadiene rubber (SBR), and cis-butadiene rubber, without using high-cost raw materials such as dual-Tg specialty rubbers. For the silica, a conventional, highly dispersible product is selected, avoiding the use of ultra-high specific surface area silica, which is difficult to disperse. The overall formulation cost is controllable, and the process conditions can be achieved on existing internal mixing equipment without special modifications. Compared to existing technologies that rely on specialty raw materials, this invention offers superior economic benefits and industrialization potential.
[0022] 6. Balanced overall performance, meeting the needs of high-end winter tires. The tread compound prepared by this invention not only exhibits excellent performance in wet skid resistance and ice and snow performance, but also maintains good levels in tensile strength, elongation at break, and wear resistance. Its rolling resistance is in the excellent range of the industry, and its comprehensive performance is balanced, which can meet the multiple requirements of high-end winter tires for safety, durability and energy saving. Detailed Implementation
[0023] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] According to a first aspect of the present invention, a method for preparing anti-slip tread rubber is provided, specifically comprising the following steps: S1, First stage of mixing: Natural rubber, solution-polymerized styrene-butadiene rubber and cis-butadiene rubber are plasticized in a mixer, and then highly dispersed silica, silica dispersant and silane coupling agent are added, mixed and discharged to obtain the first masterbatch. S2, Second stage of mixing: Highly dispersed silica and modified anti-slip resin were added to the first masterbatch and mixed to obtain the second masterbatch. S3, Third Stage Mixing: High abrasion-resistant carbon black N234, active zinc oxide, stearic acid and antioxidant are added to the second masterbatch and then mixed to obtain the third masterbatch. S4, Final Stage: Sulfur and accelerator are added to the third masterbatch, and after mixing and discharging, the mixture is passed through a two-roll mill, sheeted, and cooled to room temperature to obtain anti-slip tread rubber.
[0025] Step S1 specifically includes the following steps: After plasticizing 40-60 parts of natural rubber, 20-40 parts of solution-polymerized styrene-butadiene rubber, and 10-30 parts of butadiene rubber at room temperature for 1-3 minutes in an internal mixer, add 36-56 parts of highly dispersed silica (which accounts for 60-80% of the total amount of highly dispersed silica used in the entire process of preparing anti-slip tread rubber), 3-8 parts of silica dispersant, and 4-8 parts of silane coupling agent and mix them at 100-120℃ for 2-4 minutes. After desizing, the first masterbatch is obtained. The dispersant for the silica is zinc fatty acid soap, and the silane coupling agent is bis-[γ-(triethoxysilane)propyl]tetrasulfide; the specific surface area of the highly dispersed silica is 140-200 m² / g. 2 / g.
[0026] Step S2 specifically includes the following steps: The first masterbatch is heated to 120-130℃, and 12-28 parts of highly dispersed silica (which accounts for 20-40% of the total amount of highly dispersed silica used in the entire process of preparing anti-slip tread rubber) and 5-10 parts of modified anti-slip resin are added. The mixture is then mixed at 130-145℃ for 4-6 minutes to allow the silane coupling agent and silica to react fully, while the resin melts and forms a micro-phase separation structure with the rubber matrix, thus obtaining the second masterbatch.
[0027] In step S2, the modified anti-slip resin is a modified terpene resin, and its preparation specifically includes the following steps: Add α-pinene and bisphenol A separately into a separatory funnel, wash 2-3 times with 5wt% sodium hydroxide aqueous solution, then wash with distilled water until neutral, then add anhydrous magnesium sulfate to dry them separately, and seal for later use. Under nitrogen or argon protection, the treated α-pinene and bisphenol A are added to the reaction solvent and stirred until a homogeneous solution is formed. Then, a cationic catalyst and a molecular weight regulator are added to carry out the cationic polymerization reaction. After the polymerization reaction is completed, excess methanol is added to terminate the reaction. The reaction product is then separated and washed to remove unreacted monomers and catalyst residues. Finally, the product is subjected to vacuum distillation at 250-280℃ for 0.5-3 hours to obtain the modified anti-slip resin.
[0028] The cationic catalyst is one or more of boron trifluoride, aluminum trichloride, and ferric chloride; the molecular weight regulator is one or more of pyridine, 2-methylpyridine, and 2,6-dimethylpyridine; and the reaction solvent is one or more of toluene, xylene, and dichloromethane. The mass-volume ratio of α-pinene, bisphenol A, cationic catalyst, molecular weight regulator and reaction solvent is (1-5)g:(1-5)g:(0.05-0.25)g:(0.5-2.5)g:100mL. The cationic polymerization reaction is carried out at -20-0℃ for 0.5-3h.
[0029] The molecular weight of the modified anti-slip resin is 1000-1500 Da.
[0030] Step S3 specifically includes the following steps: The second masterbatch is cooled to 90-100℃, and 5-20 parts of high abrasion-resistant carbon black N234, 1-3 parts of active zinc oxide, 1-3 parts of stearic acid and 2-5 parts of antioxidant are added. The mixture is then kneaded at 100-110℃ for 2-3 minutes to obtain the third masterbatch. The antioxidant is obtained by mixing antioxidant 4020 and antioxidant RD in a mass ratio of 1:1.
[0031] Step S4 specifically includes the following steps: The third masterbatch is cooled to 80-90℃, and 1-2 parts of sulfur and 1-3 parts of accelerator are added. The mixture is then mixed at 90-100℃ for 1-2 minutes. After discharge, the mixture is passed through a two-roll mill 3-5 times, and the sheet is cooled to room temperature to obtain the anti-slip tread rubber. The accelerator is N-tert-butyl-2-benzothiazole sulfenamide.
[0032] According to a second aspect of the present invention, an anti-slip tread rubber is provided, which is prepared by the above-described preparation method.
[0033] To better illustrate the technical path of the present invention, the following embodiments and comparative examples are provided.
[0034] Example 1 S1, First stage of mixing: After plasticizing 5 kg of natural rubber, 3 kg of solution-polymerized styrene-butadiene rubber, and 2 kg of cis-butadiene rubber in an internal mixer at room temperature for 3 minutes, 4.55 kg of rubber with a specific surface area of 140-200 m² was added. 2The following ingredients were mixed: 0.5 kg of highly dispersed silica (purchased from Evonik Industries, model ULTRASIL®7000 GR), 0.5 kg of zinc fatty acid soap (purchased from Qingzhou Zhongrui Industry & Trade Co., Ltd.), and 0.6 kg of bis-[γ-(triethoxysilyl)propyl]tetrasulfide. The mixing conditions were 110°C for 3 min. After debinding, the first masterbatch was obtained. S2. Preparation of modified anti-slip resin: Add α-pinene and bisphenol A separately into a separatory funnel, wash three times with 5wt% sodium hydroxide aqueous solution, then wash with distilled water until neutral, and then add anhydrous magnesium sulfate to dry them separately, and seal for later use. Under nitrogen protection, 450g of treated α-pinene and 450g of bisphenol A were added to 15L of dichloromethane and stirred until a homogeneous solution was formed. Then, 22.5g of aluminum trichloride and 225g of 2,6-dimethylpyridine were added, and the reaction was carried out at -10℃ for 2h to carry out cationic polymerization. After the polymerization reaction is completed, excess methanol is added to terminate the reaction. The reaction product is then separated and washed to remove unreacted monomers and catalyst residues. Finally, vacuum distillation is carried out at 260℃ for 2 hours to obtain a modified anti-slip resin with a molecular weight of 1000-1500 Da. S3, Second Stage Mixing: The first masterbatch was heated to 125°C, and 1.95 kg of highly dispersed silica and 0.6 kg of modified anti-slip resin were added. The mixture was then kneaded at 140°C for 5 min to allow the silane coupling agent and silica to react fully, while the resin was melted and formed a micro-phase separation structure with the rubber matrix, thus obtaining the second masterbatch. S4, Third Stage Mixing: The second masterbatch was cooled to 95°C, and 1 kg of high abrasion-resistant carbon black N234, 0.2 kg of active zinc oxide, 0.2 kg of stearic acid, 0.2 kg of antioxidant 4020 and 0.2 kg of antioxidant RD were added. The mixture was then kneaded at 100°C for 3 minutes to obtain the third masterbatch. S5, Final Stage: The third masterbatch was cooled to 85°C, and 0.15 kg of sulfur and 0.25 kg of N-tert-butyl-2-benzothiazole sulfenamide were added. The mixture was then mixed at 95°C for 2 minutes. After discharge, the mixture was passed through a two-roll mill three times and then sheeted and cooled to room temperature to obtain the anti-slip tread rubber.
[0035] Example 2 S1, First stage of mixing: After plasticizing 4 kg of natural rubber, 4 kg of solution-polymerized styrene-butadiene rubber, and 2 kg of cis-butadiene rubber in an internal mixer at room temperature for 3 minutes, 4.9 kg of rubber with a specific surface area of 140-200 m² was added. 2 / g of highly dispersed silica, 0.5kg of zinc fatty acid soap, and 0.7kg of bis-[γ-(triethoxysilyl)propyl]tetrasulfide were mixed at 110℃ for 3 minutes. After debinding, the first masterbatch was obtained. S2. Preparation of modified anti-slip resin: Add α-pinene and bisphenol A separately into a separatory funnel, wash three times with 5wt% sodium hydroxide aqueous solution, then wash with distilled water until neutral, and then add anhydrous magnesium sulfate to dry them separately, and seal for later use. Under nitrogen protection, 450g of treated α-pinene and 450g of bisphenol A were added to 15L of dichloromethane and stirred until a homogeneous solution was formed. Then, 22.5g of aluminum trichloride and 225g of 2,6-dimethylpyridine were added, and the reaction was carried out at -10℃ for 2h to carry out cationic polymerization. After the polymerization reaction is completed, excess methanol is added to terminate the reaction. The reaction product is then separated and washed to remove unreacted monomers and catalyst residues. Finally, vacuum distillation is carried out at 260℃ for 2 hours to obtain a modified anti-slip resin with a molecular weight of 1000-1500 Da. S3, Second Stage Mixing: The first masterbatch was heated to 125°C, and 2.1 kg of highly dispersed silica and 0.8 kg of modified anti-slip resin were added. The mixture was then mixed at 140°C for 5 min to allow the silane coupling agent and silica to react fully, while the resin melted and formed a micro-phase separation structure with the rubber matrix, thus obtaining the second masterbatch. S4, Third Stage Mixing: The second masterbatch was cooled to 95°C, and 0.5 kg of high abrasion-resistant carbon black N234, 0.2 kg of active zinc oxide, 0.2 kg of stearic acid, 0.2 kg of antioxidant 4020 and 0.2 kg of antioxidant RD were added. The mixture was then kneaded at 100°C for 3 minutes to obtain the third masterbatch. S5, Final Stage: The third masterbatch was cooled to 85°C, and 0.15 kg of sulfur and 0.25 kg of N-tert-butyl-2-benzothiazole sulfenamide were added. The mixture was then mixed at 95°C for 2 minutes. After discharge, the mixture was passed through a two-roll mill three times and then sheeted and cooled to room temperature to obtain the anti-slip tread rubber.
[0036] Comparative Example 1 S1, First stage of mixing: 5.5 kg of natural rubber, 3.4 kg of solution-polymerized styrene-butadiene rubber, 2 kg of cis-butadiene rubber, and 0.2 kg of tackifying resin (purchased from Puyang Ruisen Petroleum Resin Co., Ltd., model: PRS®-C1085) were plasticized in an internal mixer at room temperature for 3 minutes. Then, 4.2 kg of a specific surface area of 140-200 m² was added. 2 / g of highly dispersed silica, 0.6kg of zinc fatty acid soap, and 0.6kg of bis-[γ-(triethoxysilyl)propyl]tetrasulfide were mixed at 110℃ for 3 minutes. After debinding, the first masterbatch was obtained. S2, Second stage of mixing: The first masterbatch was heated to 125°C, and 1.8 kg of highly dispersed silica and 1.6 kg of paraffinic oil were added. The mixture was then mixed at 140°C for 5 minutes to allow the silane coupling agent to fully react with the silica, while simultaneously melting the resin and forming a micro-phase separation structure with the rubber matrix, thus obtaining the second masterbatch. S3, Third Stage Mixing: The second masterbatch was cooled to 95°C, and 1 kg of high abrasion-resistant carbon black N234, 0.2 kg of active zinc oxide, 0.2 kg of stearic acid, 0.2 kg of antioxidant 4020 and 0.2 kg of antioxidant RD were added. The mixture was then kneaded at 100°C for 3 minutes to obtain the third masterbatch. S4, Final Stage: The third masterbatch was cooled to 85°C, and 135g of sulfur and 270g of N-tert-butyl-2-benzothiazole sulfenamide were added. The mixture was then mixed at 95°C for 2 minutes. After discharge, the mixture was passed through a two-roll mill three times and then sheeted and cooled to room temperature to obtain the anti-slip tread rubber.
[0037] Comparative Example 2 S1, First stage of mixing: After plasticizing 7 kg of natural rubber and 3 kg of 2Tg solution-polymerized styrene-butadiene rubber in an internal mixer at room temperature for 3 minutes, 1.05 kg of rubber with a specific surface area of 220-330 m² was added. 2 / g of highly dispersed silica and 0.15kg of bis-[γ-(triethoxysilane)propyl]tetrasulfide were mixed at 110℃ for 3min. After debinding, the first masterbatch was obtained. Among them, the solution-polymerized styrene-butadiene rubber with dual glass transition temperatures has two glass transition temperatures. Its first Tg is less than -70℃, and the second Tg temperature ranges from -55℃ to -35℃. Moreover, its peak loss factor is lower than that of ordinary solution-polymerized styrene-butadiene rubber with a single glass transition temperature. S2. Preparation of modified anti-slip resin: Add α-pinene and bisphenol A separately into a separatory funnel, wash three times with 5wt% sodium hydroxide aqueous solution, then wash with distilled water until neutral, and then add anhydrous magnesium sulfate to dry them separately, and seal for later use. Under nitrogen protection, 450g of treated α-pinene and 450g of bisphenol A were added to 15L of dichloromethane and stirred until a homogeneous solution was formed. Then, 22.5g of aluminum trichloride and 225g of 2,6-dimethylpyridine were added, and the reaction was carried out at -10℃ for 2h to carry out cationic polymerization. After the polymerization reaction is completed, excess methanol is added to terminate the reaction. The reaction product is then separated and washed to remove unreacted monomers and catalyst residues. Finally, vacuum distillation is carried out at 260℃ for 2 hours to obtain a modified anti-slip resin with a molecular weight of 1000-1500 Da. S3, Second Stage Mixing: The first masterbatch was heated to 125°C, and 0.45 kg of highly dispersed silica and 0.5 kg of modified anti-slip resin were added. The mixture was then kneaded at 140°C for 5 min to allow the silane coupling agent and silica to react fully, while the resin was melted and formed a micro-phase separation structure with the rubber matrix, thus obtaining the second masterbatch. S4, Third Stage Mixing: The second masterbatch was cooled to 95°C, and 5 kg of high abrasion-resistant carbon black N234, 0.2 kg of active zinc oxide, 0.2 kg of stearic acid, 0.15 kg of antioxidant 4020 and 0.15 kg of antioxidant RD were added. The mixture was then kneaded at 100°C for 3 minutes to obtain the third masterbatch. S5, Final Stage: The third masterbatch was cooled to 85°C, and 0.15 kg of sulfur and 0.13 kg of N-tert-butyl-2-benzothiazole sulfenamide were added. The mixture was then mixed at 95°C for 2 minutes. After discharge, the mixture was passed through a two-roll mill three times and then sheeted and cooled to room temperature to obtain the anti-slip tread rubber.
[0038] Comparative Example 3 S1, Mixing: After plasticizing 5 kg of natural rubber, 3 kg of solution-polymerized styrene-butadiene rubber, 2 kg of cis-butadiene rubber, and 0.2 kg of tackifying resin in an internal mixer at room temperature for 3 minutes, 4.2 kg of a specific surface area of 140-200 m² / g is added. 2 The following ingredients were mixed: 0.6 kg of highly dispersed silica, 0.6 kg of zinc fatty acid soap silica dispersant, 0.6 kg of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, 1.8 kg of highly dispersed silica, 1.6 kg of paraffinic oil, 1 kg of high abrasion-resistant carbon black N234, 0.2 kg of active zinc oxide, 0.2 kg of stearic acid, 0.2 kg of antioxidant 4020 and 0.2 kg of antioxidant RD. The mixing conditions were 110℃ for 11 min. After debinding, the masterbatch was obtained. S2, Final Stage: The masterbatch was cooled to 85°C, and 135g of sulfur and 270g of N-tert-butyl-2-benzothiazole sulfenamide were added. The mixture was then mixed at 95°C for 2 minutes. After discharge, the mixture was passed through a two-roll mill three times and then sheeted and cooled to room temperature to obtain the anti-slip tread rubber.
[0039] Test Example 1 To verify the mechanical properties of the tread rubber prepared according to this invention, dynamic mechanical property tests were conducted on it, specifically including the following steps: Rectangular strips were cut from approximately 2mm thick anti-skid tread rubber using a dumbbell-shaped cutter with a narrow section approximately 4mm wide and 20mm long. Three parallel samples were prepared for each group of samples. The two ends of the strips were clamped in a tensile fixture with a clamping distance of approximately 15mm to ensure that the samples were in a relaxed state. The test program was set as follows: test mode: uniaxial tensile mode; frequency: 10 Hz; static strain: 1%; dynamic strain: 0.25%; static force tracking: static force is 1.1 times the dynamic force, ensuring that the samples are always under tension during the scanning process. The temperature was increased from -60℃ to 80℃ at a rate of 3℃ / min, and dynamic strain was continuously applied during the heating process. The storage modulus E' (unit: MPa), loss modulus E'', and loss factor tanδ=E'' / E' were recorded in real time. The following data were recorded: Loss factor tanδ at 0℃: used to characterize anti-slip performance, the higher the value, the better the anti-slip performance; Loss factor tanδ at -20℃: used to characterize ice and snow performance, the higher the value, the better the grip on ice and snow; Storage modulus E' at -25℃ (unit: MPa): used to characterize low-temperature flexibility; the lower the value, the better the low-temperature flexibility. The loss factor tanδ at 60℃ is used to characterize rolling resistance. The lower the value, the lower the rolling resistance. The results are recorded in Table 1.
[0040] Table 1 Dynamic mechanical properties of tread rubber
[0041] Note: "-" in the table indicates that no test was performed.
[0042] In Comparative Examples 1 and 3, paraffin-based oil was used to replace the modified antislip resin of the present invention, which could not form a micro-phase separation structure and the low-temperature performance was expected to be poor. Therefore, the storage modulus at -25℃ and tanδ at -20℃ were not tested. Comparative Example 2 uses a completely different rubber system (double TgSSBR), whose dynamic mechanical properties and temperature response characteristics are quite different from the conventional ternary rubber system of this invention. The tanδ data at -20℃ are not very comparable, so it was not included in the comparison.
[0043] Furthermore, the 0℃ tanδ data of Comparative Examples 1 and 3 are sufficient to demonstrate the advantages of the present invention in terms of anti-slip performance. The aforementioned untested items do not affect the full disclosure and inventiveness of the present invention.
[0044] As shown in Table 1, in terms of anti-slip performance, the tanδ values at 0℃ for Examples 1 and 2 reached 0.35 and 0.38, respectively, representing an improvement of over 50% compared to 0.23 in Comparative Example 3, and also showing significant advantages over 0.33 in Comparative Example 1 and 0.237 in Comparative Example 2. This is mainly attributed to two aspects: firstly, the stepwise addition of silica and the segmented temperature control process made the silanization reaction more complete and uniform, enhanced the filler-rubber interface bonding, and improved the filler network; secondly, the micro-phase separation structure formed by the modified anti-slip resin generated additional energy dissipation near 0℃, synergistically enhancing the effect with the silica network.
[0045] Regarding low-temperature resistance to ice and snow, Examples 1 and 2 achieved tanδ values of 0.58 and 0.62 at -20℃, respectively, which are superior to 0.38 in Comparative Example 3 and 0.56 in Comparative Example 1. Simultaneously, the storage modulus E' at -25℃ was as low as 12.5 MPa and 11.8 MPa, respectively, significantly lower than 15.8 MPa in Comparative Example 2. This indicates that the present invention significantly improves anti-slip performance without sacrificing low-temperature performance, and instead achieves a simultaneous improvement in ice and snow grip. The reason for this is that the resin microregions have a relatively small impact on the glass transition temperature of the rubber continuous phase, allowing the rubber compound to maintain good molecular chain mobility at low temperatures; at the same time, the optimized filler network reduces the Payne effect and minimizes dynamic hysteresis losses.
[0046] Regarding rolling resistance, the tanδ values of the embodiments at 60°C were 0.095 and 0.092, respectively. Although slightly higher than 0.089 of Comparative Example 2, they were significantly better than 0.14 of Comparative Example 3 and 0.109 of Comparative Example 1, placing them at an excellent level in the industry. This indicates that the present invention can maintain good low rolling resistance characteristics while improving anti-slip and anti-icy performance.
[0047] Test Example 2 The Akron abrasion test was performed on the tread rubbers prepared in each group according to the method of GB / T 1689-2014 "Determination of abrasion resistance of vulcanized rubber (using Akron abrasion tester)". The tensile strength and elongation at break of the rubber were determined according to the method of GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". The results are recorded in Table 2.
[0048] Table 2. Results of Akron abrasion, tensile strength and elongation at break of tread rubber for each group.
[0049] Note: "-" in the table indicates that no test was performed.
[0050] The Akron wear data for Comparative Examples 1 and 3 were not measured because paraffin-based oil was used instead of the modified anti-slip resin of this invention in the formulations of these two comparative examples, resulting in poor wear resistance. Furthermore, their tanδ data at 0°C already sufficiently demonstrated the deterioration of anti-slip performance, so no further wear resistance tests were conducted.
[0051] As shown in Table 2, in terms of physical and mechanical properties and wear resistance, the tensile strength and elongation at break of Examples 1 and 2 remained at a high level; the Akron abrasion loss was further reduced to 0.108-0.118 cm. 3 / 1.61km, which is better than the 0.128 of Comparative Example 2, indicating that the construction of the hybrid filler network effectively improves the wear resistance of the rubber compound.
[0052] Compared to Comparative Example 3, the tensile strength and elongation at break of the embodiment are significantly improved. This is because in Comparative Example 3, the tackifying resin was added during the first stage of mixing, and after subsequent high-temperature mixing, some of it underwent thermal degradation, losing its toughening effect. At the same time, the addition of paraffinic oil weakened the filler-rubber interface bonding. In contrast, the present invention, through the stepwise addition of silica and the segmented temperature control process, allows the silanization reaction to proceed fully, enhancing the filler-rubber interface bonding. Simultaneously, the modified anti-slip resin is added synchronously with fresh silica in the second stage, forming nanoscale enriched micro-regions after cooling. These micro-regions effectively absorb and disperse energy under stress, thereby simultaneously improving both strength and toughness.
[0053] Comparative Example 2 exhibits higher tensile strength due to the high amount of carbon black used for reinforcement, but its elongation at break is significantly lower than that of the Example. This indicates that simple carbon black reinforcement makes the rubber compound brittle, while the silica-resin synergistic reinforcement system of the present invention provides the rubber compound with superior flexibility while ensuring strength.
[0054] In terms of wear resistance, the Akron wear of the embodiment is better than that of Comparative Example 2, indicating that the silica-rubber interface constructed by the present invention has stronger bonding and a more complete filler network, which effectively inhibits the shedding of fillers during dynamic wear, thereby improving the wear resistance of the rubber compound.
[0055] In summary, this invention, through a synergistic process combination of stepwise addition of silica, segmented temperature-controlled mixing, and in-situ phase separation of resin, achieves a synergistic improvement in both wet skid resistance and ice and snow performance while using conventional raw materials. Its effect is not only superior to the traditional single-feeding process, but also significantly superior to the process of adding materials in stages combined with special rubbers, demonstrating outstanding substantive features and significant progress.
[0056] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a wet-slip tread rubber, characterized in that, Specifically, the following steps are included: S1, First stage of mixing: Natural rubber, solution-polymerized styrene-butadiene rubber and cis-butadiene rubber are plasticized in a mixer, and then highly dispersed silica, silica dispersant and silane coupling agent are added, mixed and discharged to obtain the first masterbatch. S2, Second stage of mixing: Highly dispersed silica and modified anti-slip resin were added to the first masterbatch and mixed to obtain the second masterbatch. S3, Third Stage Mixing: High abrasion-resistant carbon black N234, active zinc oxide, stearic acid and antioxidant are added to the second masterbatch and then mixed to obtain the third masterbatch. S4, Final Stage: Sulfur and accelerator are added to the third masterbatch, and after mixing and discharging, the mixture is passed through a two-roll mill, sheeted, and cooled to room temperature to obtain anti-slip tread rubber.
2. The method for preparing the anti-slip tread rubber as described in claim 1, characterized in that, Step S1 specifically includes the following steps: After plasticizing 40-60 parts of natural rubber, 20-40 parts of solution-polymerized styrene-butadiene rubber, and 10-30 parts of butadiene rubber at room temperature for 1-3 minutes in an internal mixer, add 36-56 parts of highly dispersed silica (which accounts for 60-80% of the total amount of highly dispersed silica used in the entire process of preparing anti-slip tread rubber), 3-8 parts of silica dispersant, and 4-8 parts of silane coupling agent and mix them at 100-120℃ for 2-4 minutes. After desizing, the first masterbatch is obtained. The silica dispersant is a zinc fatty acid soap, and the silane coupling agent is bis-[γ-(triethoxysilane)propyl]tetrasulfide; the specific surface area of the highly dispersed silica is 140-200 m² / g. 2 / g.
3. The method for preparing the anti-slip tread rubber as described in claim 1, characterized in that, Step S2 specifically includes the following steps: The first masterbatch is heated to 120-130℃, and 12-28 parts of highly dispersed silica (which accounts for 20-40% of the total amount of highly dispersed silica used in the entire process of preparing anti-slip tread rubber) and 5-10 parts of modified anti-slip resin are added. The mixture is then mixed at 130-145℃ for 4-6 minutes to allow the silane coupling agent and silica to react fully, while the resin melts and forms a micro-phase separation structure with the rubber matrix, thus obtaining the second masterbatch.
4. The method for preparing the anti-slip tread rubber as described in claim 3, characterized in that, The modified anti-slip resin mentioned in step S2 is a modified terpene resin, and its preparation specifically includes the following steps: Add α-pinene and bisphenol A separately into a separatory funnel, wash 2-3 times with 5wt% sodium hydroxide aqueous solution, then wash with distilled water until neutral, then add anhydrous magnesium sulfate to dry them separately, and seal for later use. Under nitrogen or argon protection, the treated α-pinene and bisphenol A are added to the reaction solvent and stirred until a homogeneous solution is formed. Then, a cationic catalyst and a molecular weight regulator are added to carry out the cationic polymerization reaction. After the polymerization reaction is completed, excess methanol is added to terminate the reaction. The reaction product is then separated and washed to remove unreacted monomers and catalyst residues. Finally, the product is subjected to vacuum distillation at 250-280℃ for 0.5-3 hours to obtain the modified anti-slip resin.
5. The method for preparing the anti-slip tread rubber as described in claim 4, characterized in that, The cationic catalyst is one or more of boron trifluoride, aluminum trichloride, and ferric chloride; the molecular weight regulator is one or more of pyridine, 2-methylpyridine, and 2,6-dimethylpyridine; and the reaction solvent is one or more of toluene, xylene, and dichloromethane. The mass-volume ratio of α-pinene, bisphenol A, cationic catalyst, molecular weight regulator and reaction solvent is (1-5)g:(1-5)g:(0.05-0.25)g:(0.5-2.5)g:100mL, and the cationic polymerization reaction is carried out at -20-0℃ for 0.5-3h.
6. The method for preparing the anti-slip tread rubber as described in claim 4, characterized in that, The modified antislip resin has a molecular weight of 1000-1500 Da.
7. The method for preparing the anti-slip tread rubber as described in claim 1, characterized in that, Step S3 specifically includes the following steps: The second masterbatch is cooled to 90-100℃, and 5-20 parts of high abrasion-resistant carbon black N234, 1-3 parts of active zinc oxide, 1-3 parts of stearic acid and 2-5 parts of antioxidant are added. The mixture is then kneaded at 100-110℃ for 2-3 minutes to obtain the third masterbatch. The antioxidant is obtained by mixing antioxidant 4020 and antioxidant RD in a mass ratio of 1:
1.
8. The method for preparing the anti-slip tread rubber as described in claim 1, characterized in that, Step S4 specifically includes the following steps: The third masterbatch is cooled to 80-90℃, and 1-2 parts of sulfur and 1-3 parts of accelerator are added. The mixture is then mixed at 90-100℃ for 1-2 minutes. After discharge, the mixture is passed through a two-roll mill 3-5 times, and the sheet is cooled to room temperature to obtain the anti-slip tread rubber. The accelerator is N-tert-butyl-2-benzothiazole sulfenamide.
9. A type of anti-slip tread rubber, characterized in that, The tread rubber is prepared by the preparation method described in any one of claims 1-8.
10. The use of the anti-skid tread rubber prepared by the preparation method according to any one of claims 1-8 in the preparation of snow tires, winter tires or anti-skid tires.